2017
DOI: 10.1111/1477-9552.12253
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the 2013 CAP Reform on the Decoupled Payments’ Capitalisation into Land Values

Abstract: We assess the effects of the 2013 CAP reform on the capitalisation of decoupled payments in land rental values. Our estimates suggest that the reform leads to an increase in the capitalisation of decoupled payments by an additional 18 cents for each Euro of decoupled payments relative to the pre-reform situation. However, there is an important variation in the reform effects between Member States (MS) particularly between Old Member States (OMS) and New MS (NMS). In NMS, the capitalisation rate slightly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…Recent evidence confirms that the 2013 CAP reform caused land rental prices to increase relative to pre-reform conditions, and due to this effect, approximately 10.2 billion €/year is expected to be channeled outside the farming sector in the EU in the 2014-2020 period. Such a leakage effect that benefits nonfarming landowners implies further income inequalities among farmers in the EU (Ciaian et al 2017). Schmid et al (2006) claimed that, in most cases, DPs do not prevent a relevant share of European farmers from remaining in the poorest decile, and other authors (Allanson and Rocchi 2008;Mishra et al 2009) confirmed that the distribution of direct aid is largely unequal because high-income farms receive a large share of the payments, as do the wealthiest farm households (Rocchi et al 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent evidence confirms that the 2013 CAP reform caused land rental prices to increase relative to pre-reform conditions, and due to this effect, approximately 10.2 billion €/year is expected to be channeled outside the farming sector in the EU in the 2014-2020 period. Such a leakage effect that benefits nonfarming landowners implies further income inequalities among farmers in the EU (Ciaian et al 2017). Schmid et al (2006) claimed that, in most cases, DPs do not prevent a relevant share of European farmers from remaining in the poorest decile, and other authors (Allanson and Rocchi 2008;Mishra et al 2009) confirmed that the distribution of direct aid is largely unequal because high-income farms receive a large share of the payments, as do the wealthiest farm households (Rocchi et al 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…() conclude that ‘access to land is the major barrier for young farmers and new entrants’. The degree of capitalisation of direct income supports into land rents is much higher among the EUN‐13 New Member States relative to the older EU‐15 Member States (Ciaian et al., ). A high rate of capitalisation restricts the prospects for new entrant farmers who wish to compete in land rental markets and this capitalisation problem is greater in the New Member States relative to the old Member States.…”
Section: Agricultural Land Market Contextmentioning
confidence: 99%
“…In the last decade, PCS was most evident in the livestock sector, particularly dairy, considering its global markets (Freebairn, 2017) but also concerned land market. According to Ciaian, Kancs, and Espinosa (2017), on average, 27% of decoupled payments after the last reform of CAP in 2013 are channelled to non-farming landowners in the EU increasing renal fees for farmers. Although there is a consensus that agricultural markets are subject to PCS long-term, one can also find contradictory findings based on price co-integration analyses (Campiche, Bryan, Richardson, & Outlaw, 2006;Moss, 1992) The influence of agricultural policy on mitigating PCS is the most debatable part of this theory (Rizov, Pokrivcak, & Ciaian, 2013).…”
Section: Introductionmentioning
confidence: 99%